Тhe separate archetypes of the legal mentality of the Ukrainian nation in the public discourse - Shtepa, Oleksiy (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2018)
The article traces the manifestations of such ethnic archetypes of Ukrainian legal mentality as Really-Justice, Freedom-Liberty and Equality-Brotherhood. These behavioral patterns have destructive and constructive influence on domestic processes. For example, they mobilized the Ukrainian society to the struggle in the period of social upheavals and externalthreats, however, can produce legal nihilism, anarchism, nepotism etc. Overcoming the negative manifestations of these mental attitudes is possible through the development and implementation of effective state ideology in the sphere of law